Answer:7
Step-by-step explanation:
Answer:
y= -4/3 + 22
Step-by-step explanation:
y= -4/3x -1
14 = -4/3 (6) + b
14= -8 + b
22= b
Answer:
Daughter age = 3 years
Step-by-step explanation:
Let x be the age of the women and y be the age of the daughter.
Given:
After five year the sum of the women and daughter age = 40
![(x+5)+(y+5)=40](https://tex.z-dn.net/?f=%28x%2B5%29%2B%28y%2B5%29%3D40)
At present the sum of the women and daughter age
![x+5+y+5=40](https://tex.z-dn.net/?f=x%2B5%2By%2B5%3D40)
![x+y+10=40](https://tex.z-dn.net/?f=x%2By%2B10%3D40)
![x+y=40-10](https://tex.z-dn.net/?f=x%2By%3D40-10)
--------------(1)
So the sum of the present age is ![x+y=30](https://tex.z-dn.net/?f=x%2By%3D30)
The difference in their present age is 24 years.
![x-y=24](https://tex.z-dn.net/?f=x-y%3D24)
![x=24+y](https://tex.z-dn.net/?f=x%3D24%2By)
Now we substitute x value in equation 1.
![(24+y)+y=30](https://tex.z-dn.net/?f=%2824%2By%29%2By%3D30)
![24+2y=30](https://tex.z-dn.net/?f=24%2B2y%3D30)
![2y=30-24](https://tex.z-dn.net/?f=2y%3D30-24)
![2y=6](https://tex.z-dn.net/?f=2y%3D6)
![y=\frac{6}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B6%7D%7B2%7D)
![y=3\ years](https://tex.z-dn.net/?f=y%3D3%5C%20years)
Therefore, the daughter age is 3 years.
It would surely be helpful if you let us know which angles to measure!
The answer is C to this question